Pelaku dalam Pengelolaan Homestay di Kawasan Saribu Rumah Gadang Kabupaten Solok Selatan Sumatera Barat - Fondina Gusriza (Journal of Tourism and Creativity, 2021)
Saribu Rumah Gadang Region has been developing accommodation facilities that utilize the rumah gadang as homestay. Sice 2016 there are 10 rumah gadang join in the management of the homestay. Although being promote to support tourism develop, the number of tourist whose visits has not increased significantly. This paper aims to: 1) Analyze management homestay. 2) Analyzing the patterns of actors in managing homestays. This research was descriptive with a qualitative approach. Data was obtained by conducting interviews, observations and literature studies. Data analyzed was carried out using qualitative analysis with a descriptive approach that outlined data and facts obtained at the study site. The results of the study show the actors involved in management homestay are the owners homestay, Regional Government of South Solok Regency, Association of Sales of Indonesian Travel (ASATI) of West Sumatra, Kelompok Sadar Wisata (Pokdarwis) Saribu Rumah Gadang and Karang Taruna Tunas Harapan. Owners homestay play a role as managers of. The regional government of South Solok Regency and ASATI as a pioneer and assistance in developed the rumah gadang being a homestay. The actors who had the most role in managing homestays are Owners homestay, local governments and the least involved is Pokdarwis.